An evaluation of universal vouchers as a demand-side subsidy to change primary care utilization: A retrospective analysis of longitudinal services utilisation and voucher claims data from a survey cohort in Hong Kong. Issue 2 (February 2020) - Yeoh, Eng-Kiong; Yam, Carrie H.K.; Chong, Ka-Chun; Chow, Tsz-Yu; Fung, Valerie L.H.; Wong, Eliza L.Y.; Griffiths, Sian M.
Highlights: Undifferentiated voucher scheme subsidises elderly to visit private primary care providers. Public services utilisation and voucher-transaction data from a survey cohort were analysed. Using voucher was not associated with a reduction in public services utilization. Vouchers were mainly used for acute-care rather than disease prevention/chronic disease management. Voucher design needs to be reconsidered taking the context and goals of health system into account. Abstract: To incentivize private primary care utilization and reduce reliance on public healthcare services, Elderly Healthcare Voucher Scheme has been implemented to provide a voucher entitlement to entire older resident population for subsidising their purchase of unspecified primary healthcare services in the private sector. Our study assessed whether voucher usage is associated with reduced utilization of public healthcare services. We retrieved the public healthcare services utilization and voucher transaction data of a survey cohort of 551 participants, who were age eligible for the scheme since 2009, over the period 2009–2015. Our results showed that voucher usage was not associated with reduced utilization of public healthcare services and has encouraged dual utilization of public and private healthcare. It may be due to a generated supply-induced demand and price inflation. The finding suggests the voucher is specifically designed to address the health systems issues to achieve the effective policy objectives. Defining the specific services to be provided and the prices at which they should be offered based on the needs of specified populations is a fundamental design parameter which needs to be incorporated. The alternatives of whether primary care services should be expanded and provided in the public sector or purchased using supply/demand side instruments should be considered taking the context and goals of the health system into account.